Experiencing Society and the Lived Welfare State - Haapala, Pertti; Harjula, Minna; Kokko, Heikki (Palgrave Studies in the History of Experience, 2023)
This open access book presents a new approach to the history of welfare state. By applying the concepts of experiencing society and the lived welfare state, the collection introduces theoretical, methodological and empirical insights for bridging the everyday life and institutional structures. The chapters analyze how the welfare state as a particular individual-society relationship has become an integral part of living in the modern society. With a long-term perspective, the chapters explore the experience of society which enabled the building and the resilience of a welfare state. As the welfare state is not a universal model of social development but historically unique in different contexts, the book broadens the focus from the Nordic countries to Southern Europe, colonial Asia and post-colonial South America. This collection is essential reading for scholars and students in the social sciences and history, as well as for policymakers and practitioners who face the contemporary and future challenges of the welfare states.